1986
DOI: 10.1139/v86-137
|View full text |Cite
|
Sign up to set email alerts
|

The structures of huperzine A and B, two new alkaloids exhibiting marked anticholinesterase activity

Abstract: BAO-FENG QI. Can. J. Chem. 64, 837 (1986).Huperzine A and B, two new Lycopodium alkaloids isolated from Huperzia serrata (Thunb.) Trev., are shown to possess structures 1 and 3, respectively, on the basis of chemical and spectroscopic data.JIA-SEN LIU, YUAN-LONG ZHU, CHAO-MEI Yu, YOU-ZUO ZHOU, YAN-YI HAN, FENG-WU WU et BAO-FENG QI. Can. J. Chem. 64, 837 (1986).En se basant sur des donnCes chimiques et spectroscopiques, on dkmontre que les deux nouveaux alkaloi'des du Lycopodium, les huperzines A et B, qui ont … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
201
1
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(217 citation statements)
references
References 3 publications
6
201
1
4
Order By: Relevance
“…flowerless and primitive fern plants, rich in so-called "Lycopodium alkaloids" that have quinolizine, pyridine, and alpha-pyridone chemical skeletons [21]. These plants have a long history of use in Chinese folk medicine for the treatment of many ailments [22], but the genus has gained a worldwide reputation after the isolation of huperzine A from Huperzia serrata [23,24]. Huperzine A is a potent, reversible and selective acetylcholinesterase inhibitor [25] and is promising for treatment of symptoms of Alzheimer's disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…flowerless and primitive fern plants, rich in so-called "Lycopodium alkaloids" that have quinolizine, pyridine, and alpha-pyridone chemical skeletons [21]. These plants have a long history of use in Chinese folk medicine for the treatment of many ailments [22], but the genus has gained a worldwide reputation after the isolation of huperzine A from Huperzia serrata [23,24]. Huperzine A is a potent, reversible and selective acetylcholinesterase inhibitor [25] and is promising for treatment of symptoms of Alzheimer's disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…The hydration reaction, performed in aqueous ethanol at 70 °C, with 5 mol% of 1, allowed the quantitative conversion of 3 to the corresponding amide 4. (−)-Huperzine A (9) is a tricyclic alkaloid produced by the Chinese herb Hupercia serrata [26], with intense contemporary interest in clinical application for treating neurodegenerative diseases [27][28][29]. Several total syntheses of 9 have been reported [27][28][29].…”
Section: Preparation Of Complex [Pth{(pme 2 O) 2 H}(pme 2 Oh)] Firstmentioning
confidence: 99%
“…cleroda-3,14-diene Raja et al, 1995;Zakaria et al, 2008 26 Psilotum nudum Quercetin, kaempferol, amentoflavone, hinokiflavone, vicenin-2 psilotin, and 3'-hydroxypsilotin Cambie and Ash, 1994 27 Huperzia selago Huperzine A Staerk et al, 2004 28 Huperzia serrata Alkaloids: huperzine A and B Liu et al, 1986 29 Pityrogramma tartarea 2'6'-dihydroxy-4,4'-dimethoxydihydrochalcone, kaempferol 7-methyl ether, and apigenin 7-methyl ether Star and Mabry, 1971 30 Yang et al, 2013 compounds are found only in the genus Dryopteris, which has been used in chemosystematic and phylogenetic studies (Widen, 1971;Britton, 1971a, 1971b). Flavonoids and phenolic compounds are the most general group of bioactive principles in plants, occurring in almost all plant parts, but mainly in photosynthesizing cells.…”
Section: Phytochemicals Of Ferns and Their Distribution In Other Planmentioning
confidence: 99%